Transcriptomic analysis of the Brazilian blind characid, Stygichthys typhlops, reveals convergent selection with Astyanax mexicanus and other cavefishes - Arcila, Dahiana; Rincon-Sandoval, Melissa; Hanson, William; Hart, Pamela B.; González, Vanessa L.; Betancur-R, Ricardo; Bichuette, Maria E. (Frontiers in Ecology and Evolution, 2023)
Molecular studies have shown that Neotropical fishes of the order Characiformes have undergone two independent events of cave colonization. Among these fishes are the Mexican blind cavefish (Astyanax mexicanus), a well-studied model system for cave adaptation, and the lesser-known Brazilian blind characid (Stygichthys typhlops). Although various genomic and transcriptomic approaches have been used to identify genes responsible for cave adaptation in A. mexicanus, these genetic factors have not been explored in an evolutionary comparative framework in cave-adapted characiforms. To address this gap, we assembled a de novo transcriptome for the Brazilian blind characid, identifying 27,845 assembled unigenes, of which 22,580 were assigned as putative one-to-one orthologs to the Mexican cavefish. We then used the package RELAX to analyze 789 genes in cavefishes, identifying 311 genes under intensified or relaxed selection. Our analysis revealed 26 genes with signatures of convergent, relaxed selection linked to vision, circadian cycles, pigmentation, and hematopoiesis processes. Additionally, we conducted differential gene expression analyses between the snout region and a control tissue sample (muscle), identifying 96 differentially expressed genes associated with cell-surface-bound and calcium-binding proteins. Our study offers insights into the genetic mechanisms underlying cave adaptation in characiform fishes, particularly the Brazilian blind characid. Moreover, our transcriptome dataset and list of genes under convergent, relaxed, and intensified selection serve as a valuable resource for future functional studies of genes involved in cave adaptation. Our work highlights the importance of examining genetic adaptations in multiple independent lineages to better understand the evolutionary processes underlying cave adaptation.